Calculus with Analytic Geometry by edwards & Penney soln ch4

Calculus with Analytic Geometry

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
Section 4.1 C04S01.001: 2 x 2 y dy dx =0,so dy dx = x y . Also, y = ± x 2 1,so dy dx = ± x x 2 1 = x ± x 2 1 = x y . C04S01.002: x dy dx + y =0 ,so dy dx = y x . By substituting y = x 1 here, we get dy dx = x 1 x = x 2 , which is the result obtained by explicit diferentiation. C04S01.003: 32 x +50 y dy dx ; dy dx = 16 x 25 y . Substituting y = ± 1 5 400 16 x 2 into the derivative, we get dy dx = 16 x 5 400 16 x 2 , which is the result obtained by explicit diferentiation. C04S01.004: 3 x 2 +3 y 2 dy dx dy dx = x 2 y 2 . y = 3 1 x 3 , so substitution results in dy dx = x 2 (1 x 3 ) 2 / 3 . Explicit diferentiation yields the same answer. C04S01.005: 1 2 x 1 / 2 + 1 2 y 1 / 2 dy dx =0: dy dx = r y x . C04S01.006: 4 x 3 +2 x 2 y dy dx xy 2 +4 y 3 dy dx =0: (2 x 2 y y 3 ) dy dx = (4 x 3 xy 2 ); dy dx = 4 x 3 xy 2 2 x 2 y y 3 . C04S01.007: 2 3 x 1 / 3 + 2 3 y 1 / 3 dy dx dy dx = µ x y 1 / 3 = ³ y x ´ 1 / 3 . C04S01.008: y 2 +2( x 1) y dy dx =1, so dy dx = 1 y 2 2 y ( x 1) . C04S01.009: Given: x 3 x 2 y = xy 2 + y 3 : 3 x 2 x 2 dy dx 2 xy = y 2 xy dy dx y 2 dy dx ; 3 x 2 2 xy y 2 =(2 xy y 2 + x 2 ) dy dx ; dy dx = 3 x 2 2 xy y 2 3 y 2 xy + x 2 . C04S01.010: Given: x 5 + y 5 =5 x 2 y 2 : 5 x 4 +5 y 4 dy dx =10 x 2 y dy dx +10 xy 2 ; dy dx = 10 xy 2 5 x 4 5 y 4 10 x 2 y . C04S01.011: Given: x sin y + y sin x =1: x cos y dy dx + sin y + y cos x + sin x dy dx =0; dy dx = sin y + y cos x x cos y + sin x . 1
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
C04S01.012: Given: cos( x + y ) = sin x sin y : sin( x + y )(1 + dy dx ) = sin x cos y dy dx + sin y cos x ; dy dx = sin y cos x + sin( x + y ) sin( x + y ) + sin x cos y . C04S01.013: Given: cos 3 x + cos 3 y = sin( x + y ): 3 ( cos 2 x ) ( sin x )+3 ( cos 2 y ) ( sin y ) dy dx = cos( x + y ) µ 1+ dy dx ; dy dx = cos( x + y )+3cos 2 x sin x x + y 2 y sin y . C04S01.014: Given: xy = tan xy : x dy dx + y = ( sec 2 xy ) µ x dy dx + y ; dy dx = y sec 2 xy y x x sec 2 xy = y x . Note: The original equation is of the form tan u = u , which is true only for some isolated constant values of u ; under the assumption that xy = k for some constant k , we also obtain dy dx = y x . C04S01.015: 2 x +2 y dy dx =0 : dy dx = x y .A t ( 3 , 4) the tangent has slope 3 4 and thus equation y +4= 3 4 ( x 3). C04S01.016: x dy dx + y : dy dx = y x t ( 4 , 2) the tangent has slope 1 2 and thus equation y +2= 1 2 ( x 4). C04S01.017: x 2 dy dx xy =1 ,so dy dx = 1 2 xy x 2 t ( 2 , 1) the tangent has slope 3 4 and thus equation 3 x +4 y = 10. C04S01.018: 1 4 x 3 / 4 + 1 4 y 3 / 4 dy dx =0: dy dx = ( y/x ) 3 / 4 . At (16 , 16) the tangent has slope 1 and thus equation x + y = 32. C04S01.019: y 2 xy dy dx xy + x 2 dy dx : dy dx = 2 xy + y 2 2 xy + x 2 t ( 1 , 2) the slope is zero, so an equation of the tangent there is y = 2. C04S01.020: 1 ( x +1) 2 1 ( y 2 · dy dx , so dy dx = ( y 2 ( x 2 t ( 1 , 1) the tangent line has slope 1 and thus equation y 1= ( x 1). C04S01.021: 24 x +24 y dy dx =25 y +25 x dy dx : dy dx = 25 y 24 x 24 y 25 x t ( 3 , 4) the tangent line has slope 4 3 and thus equation 4 x =3 y .
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

This document was uploaded on 02/01/2008.

Page1 / 123

Calculus with Analytic Geometry by edwards & Penney soln...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online